Sodium acetate/sodium butyrate alleviates lipopolysaccharide-induced diarrhea in mice via regulating the gut microbiota, inflammatory cytokines, antioxidant levels, and NLRP3/Caspase-1 signaling - Chen, Xiushuang; Kong, Qinghui; Zhao, Xiaoxiao; Zhao, Chenxi; Hao, Pin; Irshad, Irfan; Lei, Hongjun; Kulyar, Muhammad Fakhar-e-Alam; Bhutta, Zeeshan Ahmad; Ashfaq, Hassan; Sha, Qiang; Li, Kun; et al. (Frontiers in Microbiology, 2022)
Diarrhea is a word-widely severe disease coupled with gastrointestinal dysfunction, especially in cattle causing huge economic losses. However, the effects of currently implemented measures are still not enough to prevent diarrhea. Present study is carried out to explore the potential effects of sodium acetate/sodium butyrate on Lipopolysaccharide induced diarrhea in mice. Fifty ICR mice were randomly divided into control (C), LPS induced (L) and sodium acetate/sodium butyrate (D, B, A) treated groups. Serum and intestine samples were collected to examine inflammatory cytokines, antioxidant levels, relative gene expressions, and gut microbiota changes. Results indicated that LPS decreased the villus height (p<0.0001), increased the crypt depth (p<0.05), and lowered the villus height to crypt depth ratio (p<0.0001), while sodium acetate/sodium butyrate supplementation caused significantl increase in the villus height (p<0.001), decrease in the crypt depth (p<0.01), and increase in the villus heightto crypt depth ratio (p<0.001), especially. In mouse treated with LPS, it was found that serum level of IL-1β, TNF-α (p<0.001) and MDA (p<0.01) was prominently higher respectively, however sodium acetate/sodium butyrate supplementation could noteworthily drop IL-1β, TNF-α (p<0.01) and MDA (p<0.01), respectively. A total of 19 genera were detected among mouse groups including Lactobacillus unidentified F16, Adlercreutzia, Ruminococcus, [Ruminococcus], Acetobacter, cc 115, Cupriavidus, Shigella, unidentified_S24-7, unclassified RF39, unclassified_Enterobacteriaceae, Pseudomonadales, Rhodococcus, unclassified Comamonadaceae, Lysobacter, Faecalibacterium, Gluconacetobacter, and Bradyrhizobiaceae. LPS treatment up-regulated the expression of ZO-1 (p<0.01) and NLRP3 (p<0.0001) in mouse, however sodium acetate/sodium butyrate solution supplementation down-regulated the expression of ZO-1 (p<0.05) and NLRP3 (p<0.05) genes in treated mouse. Also, LPS change clearly down-regulated the expression of Occludin (p<0.001), Claudin (p<0.0001) and Caspase-1 (p<0.0001) genes, while sodium acetate/sodium butyrate solution supplementation up-regulated those gene expressions in treated groups. The present study revealed sodium acetate/sodium butyrate supplementation alleviated LPS induced diarrhea in mice via enriching beneficial bacterium and decreasing pathogens, which could regulate oxidative damages, and inflammatory responses through NLRP3/Caspase-1 signaling. The current results may give insights to the prevention and treatment of diarrhea.